DISEMINASI PENGETAHUAN TOKOH KI NARTOSABDHO MELALUI EVENT FESTIVAL SEABAD NADA DAN WARISAN KI NARTOSABDHO KEPADA PEGIAT SENI MAHASISWA DI KOTA SEMARANG SEBAGAI PROJECT MANAGER, SPONSORSHIP MANAGER, MEDIA PLANNER, KOORDINATOR LAPANGAN, TENANT MANAGER - Raihan Arda Maheswara; Yohanes Thianika Budiarsa (Interaksi Online, 2026)
This study analyzes the dissemination of knowledge regarding Ki Nartosabdho throughthe cultural event “Festival Seabad Nada dan Warisan Ki Nartosabdho” targeting student artcommunities in Semarang. The increasing dominance of global popular culture hascontributed to the declining awareness of local cultural figures among younger generations.This research employs a qualitative approach with an implementation-based method, utilizingIntegrated Marketing Communication (IMC) as the conceptual framework. The festivalintegrates various communication tools, including advertising, public relations, andexperiential events. Findings reveal that the program successfully enhances participation,knowledge, and cultural appreciation among participants. The study concludes that culturalfestivals supported by integrated communication strategies can effectively bridge the gapbetween interest and knowledge in cultural preservation.